การศึกษาและวิเคราะห์เครือข่ายการท่องเที่ยวภายในประเทศไทย - กฤษฎาภฤศ ปึงภัทรกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This research focuses on the development, study, and investigation on Thai tourism network, where Network Theory and several centrality measures are applied to structurally identify the role of each tourism area in such a network. With this piece of information, the tourism authority would be able to devise efficient and sustainable tourism development plans that benefit tourism industry as a whole. Our tourism network is regarded as a weighted one, where link weights are assigned based on tourism flow among tourism areas, taken into account tourism factors such as numbers of attractions and accommodations in each area. Based on the computational results, we find that Bangkok is the most important tourism area in all aspects, and the peripheral areas close to Bangkok are supported area facilitating tourism flow to Bangkok. In addition, Chiangmai, Pattani, Ratburi, Chonburi, and Roi et provinces are identified as the center of tourism area in each region, while Nakhon Ratchasima, Prachuap Khiri Khan, Chumphon, and Nakhon Sawan serve as the gates between these tourism areas.